Directional charge delocalization dynamics in semiconducting 2H-MoS $$_{2}$$ 2 and metallic 1T-Li $$_{x}$$ x MoS $$_{2}$$ 2 - Robert Haverkamp (Nature Portfolio, 2021)
Abstract The layered dichalcogenide MoS $$_{2}$$ 2 is relevant for electrochemical Li adsorption/intercalation, in the course of which the material undergoes a concomitant structural phase transition from semiconducting 2H-MoS $$_{2}$$ 2 to metallic 1T-Li $$_{x}$$ x MoS $$_{2}$$ 2 . With the core hole clock approach at the S L $$_{1}$$ 1 X-ray absorption edge we quantify the ultrafast directional charge transfer of excited S3p electrons in-plane ( $$\parallel$$ ‖ ) and out-of-plane ( $$\perp$$ ⊥ ) for 2H-MoS $$_{2}$$ 2 as $$τ _{2H,\parallel } = 0.38 ± 0.08$$ τ 2 H , ‖ = 0.38 ± 0.08 fs and $$τ _{2H,\perp } = 0.33 ± 0.06$$ τ 2 H , ⊥ = 0.33 ± 0.06 fs and for 1T-Li $$_{x}$$ x MoS $$_{2}$$ 2 as $$τ _{1T,\parallel } = 0.32 ± 0.12$$ τ 1 T , ‖ = 0.32 ± 0.12 fs and $$τ _{1T,\perp } = 0.09 ± 0.07$$ τ 1 T , ⊥ = 0.09 ± 0.07 fs. The isotropic charge delocalization of S3p electrons in the semiconducting 2H phase within the S-Mo-S sheets is assigned to the specific symmetry of the Mo-S bonding arrangement. Formation of 1T-Li $$_{x}$$ x MoS $$_{2}$$ 2 by lithiation accelerates the in-plane charge transfer by a factor of $$\sim 1.2$$ ∼ 1.2 due to electron injection to the Mo-S covalent bonds and concomitant structural repositioning of S atoms within the S-Mo-S sheets. For excitation into out-of-plane orbitals, an accelerated charge transfer by a factor of $$\sim 3.7$$ ∼ 3.7 upon lithiation occurs due to S-Li coupling.